(untitled) (Baghdad Science Journal, 2007)
Oral swab samples were collected from 120 children (ages between one month- 10 years) who were infected with oral thrush and 30 healthy children. The percentages of isolated yeasts and Bacteria were 66.6% and 96.6% respectively. The dominate yeast and bacteria were Candida albicans and Staphylococcus aureus with of 78.7% and 34.4% respectively. Results revealed that the highest percent of infection with oral thrush disease was 32.5% in children within the age of 1-2 months.